1990
DOI: 10.1016/0741-5214(90)90145-z
|View full text |Cite
|
Sign up to set email alerts
|

The use of composite grafts in femorocrural bypasses performed for limb salvage: A review of 108 consecutive cases and comparison with 57 in situ saphenous vein bypasses

Abstract: We retrospectively reviewed the results of 108 consecutive femorocrural bypasses performed with prosthetic/autogenous composite graft material and compared these with the results of 57 crural bypasses using greater saphenous vein by the in situ technique. Indication for operation in all cases was the salvage of an otherwise imminently threatened limb. Polytetrafluoroethylene-composite grafts (n = 87) and human umbilical vein-composite grafts (n = 21) were placed only in patients lacking suitable autogenous mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…One of the most important determinants for early outcome of infrainguinal reconstructions is the outflow resistance as judged by the angiographic runoff status. 2,4,8,9 Proper selection of patients and exclusion from operative consideration of cases with poor runoff will result in a low early failure rate.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important determinants for early outcome of infrainguinal reconstructions is the outflow resistance as judged by the angiographic runoff status. 2,4,8,9 Proper selection of patients and exclusion from operative consideration of cases with poor runoff will result in a low early failure rate.…”
Section: Discussionmentioning
confidence: 99%
“…Because we were dissatisfied with externally tunneled bypasses to the anterior tibial artery, in terms of skin complications, and empirically thought that the anatomic route would enable the conduit to assume a more harmonious adaptation to the knee joint when crossing through the interosseous membrane, we began to tunnel grafts directed to the anterior tibial artery in an anatomic fashion. Overall patency of this series is 50% at 3 years, with a limb salvage rate of 70% for the same interval: this is within the overall standard results of distal revascularization [1,2,4,5,10,11].…”
Section: Discussionmentioning
confidence: 66%
“…The best patency rates are achieved with autologous saphenous vein as a conduit, no matter whether inversed or "in situ" [2,5,11]; nevertheless, when fully autologous vein material is lacking acceptably good patency rates can be achieved with composite grafts as well [4]. Information about wound complications and length of hospitalization are somewhat lacking in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Second, only an autogenous vein of good quality with a large diameter must be used. Prior studies have reported unfavorable outcomes of composite prosthetic-autogenous grafts [11,23,24]; however, these studies have a possibility of selection bias, and the details of the procedures using composite grafts were not well described. Third, the operation must be performed in a planned manner.…”
Section: Discussionmentioning
confidence: 99%